Sosialisasi Tanaman Toga Pelancar Asi Di Daerah Limbungan RW 08 Kelurahan Rumbai Pesisir Kota Pekanbaru - Febriani, Ade; Erick Caesarrani; Novi Elvira; Sellia Juwita; Wahyu Margi Sidoretno; Siti Aisyah (LPPM UMRI, 2022)
This community service activity program is so that mothers, especially breastfeeding mothers, can know the types and benefits of the toga plant to facilitate breastfeeding. This community service is carried out in the form of counseling and implementation of the introduction of special toga plants to facilitate breastfeeding for breastfeeding mothers directly and planting toga plants in the area around the mother's house (respondents). Community service consists of 2 stages, the first stage is collecting data on breastfeeding mothers and planting toga seedlings and the second stage is the distribution of seeds which will be carried out during the posyandu schedule in the Limbungan RW 08 Kelurahan Rumbai Pesisir, namely on June 08 2022. the result of this community service activity is a good response from the respondents. Participants are able and have been able to do processing and understand about the toga plant to facilitate the production of breast milk. During the activity, it was found that the mother's knowledge about the toga plant to increase breast milk was good and all the audience understood about the toga plant to increase breast milk.